KONSTRUKTIVISME SEBAGAI RESISTENSI TERHADAP KRISIS REFLEKSI GENERASI Z DI ERA DIGITAL - Anang Wijatmiko; Khamim Qolili; Prasetyo Karyo Utomo; Febrian Afirsta Kusumajaya; Nanda Hasnan Fardany; Arief Rahman Yusuf (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Generation Z, as digital natives, faces serious challenges in vocational education, particularly in the Software Engineering (RPL) program. Observations at SMKN 1 Ponorogo reveal a reflection crisis, where students rely heavily on short tutorials from YouTube or online forums to complete assignments. This pattern creates a culture of tutorialism and illusion of competence, in which technical success is considered sufficient without conceptual understanding or social awareness. The urgency of this study lies in the need to restore reflective meaning in digital vocational education so that it does not merely produce compliant technicians but individuals who are critical and responsible. This research aims to examine constructivism as a paradigm of resistance to the reflection crisis of Generation Z. The study employs a qualitative descriptive approach with a case study design. Data were collected through participatory observation, in-depth interviews with students and teachers, documentation, and focus group discussions (FGD). Thematic analysis was applied with source and method triangulation to ensure validity. The findings highlight four key aspects: (1) the emergence of tutorialism and illusion of competence in RPL learning; (2) an epistemological crisis underlying shallow technical practices; (3) constructivism functioning as a form of pedagogical resistance to the instant digital culture; and (4) the reconstruction of the RPL teacher’s role as a facilitator of critical reflection, emphasizing process rather than mere outcomes. In conclusion, constructivism is not only a learning strategy but also a pedagogical paradigm capable of restoring reflection as the core of vocational education in the digital era. ABSTRAK Generasi Z sebagai digital native menghadapi tantangan serius dalam pembelajaran vokasi, khususnya di jurusan Rekayasa Perangkat Lunak (RPL). Observasi di SMKN 1 Ponorogo menunjukkan adanya krisis refleksi, di mana siswa lebih banyak mengandalkan tutorial singkat dari YouTube atau forum daring untuk menyelesaikan tugas. Pola ini melahirkan budaya tutorialisme dan ilusi kompetensi, yaitu keberhasilan teknis dianggap cukup tanpa pemahaman konseptual maupun kesadaran sosial. Urgensi penelitian ini terletak pada kebutuhan mendesak untuk mengembalikan makna reflektif dalam pendidikan vokasi digital agar tidak sekadar melahirkan teknisi patuh, tetapi individu yang kritis dan bertanggung jawab.Penelitian ini bertujuan menelaah konstruktivisme sebagai paradigma resistensi terhadap krisis refleksi generasi Z. Metode yang digunakan adalah kualitatif deskriptif dengan desain studi kasus. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan siswa dan guru, dokumentasi, serta focus group discussion (FGD). Analisis dilakukan secara tematik dengan triangulasi sumber dan metode untuk menjaga validitas. Temuan penelitian menunjukkan empat hal utama: (1) munculnya budaya tutorialisme dan ilusi kompetensi dalam pembelajaran RPL; (2) adanya krisis epistemologis di balik praktik teknis yang dangkal; (3) konstruktivisme berfungsi sebagai bentuk resistensi pedagogis terhadap budaya instan digital; dan (4) rekonstruksi peran guru RPL sebagai fasilitator refleksi kritis yang menekankan proses, bukan sekadar hasil. Sehingga,konstruktivisme bukan hanya strategi pembelajaran, tetapi juga paradigma pedagogis yang mampu mengembalikan refleksi sebagai inti pendidikan vokasi di era digital.